2021
DOI: 10.1155/2021/1743677
|View full text |Cite|
|
Sign up to set email alerts
|

Observation on the Effect of Bone Grafting Alone and Guided Tissue Regeneration Combined with Bone Grafting to Repair Periodontal Intraosseous Defects

Abstract: Objective. To investigate the curative effect of guided tissue regeneration (GTR) combined with bone grafting and improve the aesthetic appearance of patients’ gingiva. Methods. A total of 86 patients with periodontal intraosseous defects were selected from February 2019 to February 2021. All the patients were divided into a control group and an observation group according to the random number table, with 43 patients in each group. Bone grafting was performed in the control group, while GTR was additionally us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…This limits their widespread use as a primary treatment for periodontitis. Several studies have demonstrated the effectiveness of bone grafting in improving clinical outcomes in periodontal regeneration, although more long-term randomized controlled trials are needed to establish their efficacy and safety [ 39 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This limits their widespread use as a primary treatment for periodontitis. Several studies have demonstrated the effectiveness of bone grafting in improving clinical outcomes in periodontal regeneration, although more long-term randomized controlled trials are needed to establish their efficacy and safety [ 39 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…PRF enhances wound healing and regeneration and several studies have shown rapid and accelerated woundhealing with the use of PRF than without it 5 . It showed that the GTR combined with bone grafting was better than bone grafting alone in improving the aesthetics of the patients' gums, which might be related to its promotion of soft tissue healing and good integration of soft tissues 6 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that guided tissue regeneration with bone replacement or transplantation may improve clinical outcomes of periodontal intraosseous defects [ 12 , 13 ]. The physiological traits of bone grafts and bone substitute materials (BSM) are typically described using osteoinduction, osteoconduction, and osteogenesis [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%